Policy-into-practice for rheumatoid arthritis: Randomized controlled trial and cohort study of E-learning targeting improved physiotherapy management - Fary, Robyn; Slater, Helen; Chua, J.; Ranelli, Sonia; Chan, M.; Briggs, Andrew (John Wiley and Sons Inc., 2015)
Objective To examine the effectiveness of a physiotherapy-specific, web-based e-learning platform, "RAP-el," in best-practice management of rheumatoid arthritis (RA) using a single-blind, randomized controlled trial (RCT) and prospective cohort study. Methods Australian-registered physiotherapists were electronically randomized into intervention and control groups. The intervention group accessed RAP-eL over 4 weeks. Change in self-reported confidence in knowledge and skills was compared between groups at the end of the RCT using linear regression conditioned for baseline scores by a blinded assessor, using intent-to-treat analysis. Secondary outcomes included physiotherapists' satisfaction with RA management and responses to RA-relevant clinical statements and practice-relevant vignettes. Retention was evaluated in a cohort study 8 weeks after the RCT. Results Eighty physiotherapists were randomized into the intervention and 79 into the control groups. Fifty-six and 48, respectively, provided baseline data. Significant between-group differences were observed for change in confidence in knowledge (mean difference 8.51; 95% confidence interval [95% CI] 6.29, 10.73; effect size 1.62) and skills (mean difference 7.26; 95% CI 5.1, 9.4; effect size 1.54), with the intervention group performing better. Satisfaction in ability to manage RA, 4 of the 6 clinical statements, and responses to vignettes demonstrated significant improvement in the intervention group. Although 8-week scores showed declines in most outcomes, their clinical significance remains uncertain. Conclusion RAP-eL can improve self-reported confidence, likely practice behaviors and satisfaction in physiotherapists' ability to manage people with RA, and improve their clinical knowledge in several areas of best-practice RA management in the short term.